Effectiveness of Acceptance and Commitment Therapy on Conflict Resolution Strategies in Conflicting Couples - Farajullah Khosravi; Seyed Mahmood Mirzamani Bafghi; Marjan Jaafari Roshan (Iranian Evolutionary Educational Psychology Journal, 2025)
Objective: The aim of this study was to determine the effectiveness of acceptance and commitment therapy on conflict resolution strategies in conflicting couples in Kermanshah. Methods: The research methodology employed was semi-experimental in nature and was implemented as a pre-test-post-test design with a control cohort. The statistical population for this investigation encompassed all conflicting couples seeking assistance at counseling centers in Kermanshah during the year 2021. The sample comprised two groups, each consisting of 15 individuals, who were selected through simple random sampling and subsequently assigned to either the experimental or control group at random. Data collection was facilitated through the utilization of Rahim's Conflict Resolution Styles Questionnaire. To examine the hypotheses, a multivariate analysis of covariance was employed. Results: The findings indicated that acceptance and commitment therapy yielded a statistically significant enhancement in conflict resolution styles among couples in the experimental group (P <0.001). Conclusions: Overall, the results substantiate the efficacy of acceptance and commitment therapy in fostering conflict resolution strategies among discordant couples.